Facing death & dying well [videorecording (DVD)] - Bstan- dzin-rgya-mtsho, Dalai Lama XIV, 1935- (Meridian Trust, 2011)
H.H. The Dalai Lama teaches about the truth of suffering, the Three Characteristics of Existence, and the dissolution of the body's elements at death. Meditating on impermanence and the momentary changing nature of existence helps viewers appreciate the basic unsatisfactory nature of existence, and strive towards liberation. His Holiness encourages viewers to develop an awareness of death and move from gross understanding to more subtle levels. Presented in a mixture of Tibetan and English.